Addressing Employee Inefficiency to Reduce Problematic Debts in Uzbek Banks: Operational and Process Improvement Approaches - Temirov Abdumalik Temirovich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: Rising problematic debts in banks of Uzbekistan are closely linked to operational inefficiencies among employees. Ineffective workflows, insufficient training, and poor monitoring contribute to delays in identifying delinquent accounts and inadequate debt recovery. This study investigates operational strategies to mitigate employee inefficiency and enhance the realization of non-performing loans. Using portfolio analysis and structured interviews with 50 bank professionals, the research identifies gaps in workflows, monitoring, and accountability. Findings suggest that process standardization, digital monitoring tools, and targeted operational training significantly reduce problematic debt growth and improve recovery efficiency.